2018
DOI: 10.1016/j.chom.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Flaviviruses Exploit the Lipid Droplet Protein AUP1 to Trigger Lipophagy and Drive Virus Production

Abstract: Ubiquitylation is one of the most versatile protein post-translational modifications and is frequently altered during virus infections. Here we employed a functional proteomics screen to identify host proteins that are differentially ubiquitylated upon dengue virus (DENV) infection. Among the several differentially modified proteins identified in infected cells was AUP1, a lipid droplet-localized type-III membrane protein, which exists predominantly in the mono-ubiquitylated form. AUP1 associated with DENV NS4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(191 citation statements)
references
References 49 publications
3
188
0
Order By: Relevance
“…AUP1 was regulated by monoubiquitin modification, where infection or a combined expression of viral NS4A and NS4B were necessary and sufficient to generate the unmodified form of AUP1 -a step that was critical in induction of this pathway. Interestingly, loss of AUP1 did not affect viral replication; however, impaired autophagy was accompanied by degradation of viral proteins through the proteasomal pathway resulting in significantly reduced production of progeny virions, supporting a specific role of AUP1-dependent lipophagy in assembly of virus particles [16]. These results were in agreement with an independent report demonstrating expression of Dengue NS4A was sufficient to trigger autophagy and protect against cell death.…”
Section: Hh Wong and S Sanyal Seminars In Cell And Developmental Bsupporting
confidence: 89%
See 3 more Smart Citations
“…AUP1 was regulated by monoubiquitin modification, where infection or a combined expression of viral NS4A and NS4B were necessary and sufficient to generate the unmodified form of AUP1 -a step that was critical in induction of this pathway. Interestingly, loss of AUP1 did not affect viral replication; however, impaired autophagy was accompanied by degradation of viral proteins through the proteasomal pathway resulting in significantly reduced production of progeny virions, supporting a specific role of AUP1-dependent lipophagy in assembly of virus particles [16]. These results were in agreement with an independent report demonstrating expression of Dengue NS4A was sufficient to trigger autophagy and protect against cell death.…”
Section: Hh Wong and S Sanyal Seminars In Cell And Developmental Bsupporting
confidence: 89%
“…DENV non-structural protein NS1 and dsRNA were reported to co-localise with LC3 and ribosomal proteins [38,39]. Another study described the induction of LC3+ vesicles, which colocalised with NS4A in infected cells, or when transfected with a combination of DENV NS4A and NS4B [16]. This was independently corroborated by ZIKV infection in human fetal neural stem cells where expression of NS4A and NS4B were sufficient to block neurogenesis and promote autophagy, displaying partial colocalisation with LC3+ vesicles [53].…”
Section: Autophagosomes As Viral Replication Sitesmentioning
confidence: 88%
See 2 more Smart Citations
“…To achieve this, viral proteins (especially nonstructural protein 3—NS3) sequester the fatty acid synthase (FASN) and 3‐hydroxy‐3‐methyl‐glutaryl‐CoA reductase (HMGCR) to the RC, resulting in increased cholesterol uptake and synthesis of triacylglycerol after viral infection . DENV was also recently related to regulate the degradation of the host lipid droplet; it has been shown that a viral protein (NS4A) exploits the acyltransferase activity of AUP1, a lipid droplet‐localized type‐III membrane protein, to trigger lipophagy . In addition, some cholesterol uptake receptors, such as the low‐density lipoprotein receptor (LDLr), are known to participate during DENV infection, making it possible to identify the changes in lipid metabolism during DENV infection that can be used to develop new biomarkers of disease severity .…”
Section: Introductionmentioning
confidence: 99%